2015
DOI: 10.1108/bfj-04-2014-0141
|View full text |Cite
|
Sign up to set email alerts
|

Status of prerequisite programs for the implementation of HACCP system in chain restaurants in Iran

Abstract: Purpose – The purpose of this paper is to evaluate the compliance status of prerequisite programs (PRPs) and to determine the feasibility of hazard analysis and critical control point (HACCP) program in restaurants in different cities of Iran. Design/methodology/approach – In total, 58 great chain restaurants were assessed randomly by observation, interview and questionnaires. The main prerequisites for HACCP implementation in questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Dari keempat variabel pemahaman penerapan IMS yang memiliki nilai koefisien tertinggi dan memiliki pengaruh paling besar pada kinerja fokus eksternal karyawan adalah aspek pelanggan yaitu sebesar 0,379. Ukuran kepuasan pelanggan memberikan umpan balik mengenai seberapa baik perusahaan dalam menunjukkan loyalitas dan profitabilitas dalam pelayanan (Tavakkoli et al, 2015). Perusahaan yang tidak dapat memahami kebutuhan pelangan akan memudahkan para pesaing untuk menyerang melalui penawaran produk yang lebih baik yang sesuai dengan keinginan pelanggan (Kaplan dan Norton, 2000).…”
Section: (7)unclassified
“…Dari keempat variabel pemahaman penerapan IMS yang memiliki nilai koefisien tertinggi dan memiliki pengaruh paling besar pada kinerja fokus eksternal karyawan adalah aspek pelanggan yaitu sebesar 0,379. Ukuran kepuasan pelanggan memberikan umpan balik mengenai seberapa baik perusahaan dalam menunjukkan loyalitas dan profitabilitas dalam pelayanan (Tavakkoli et al, 2015). Perusahaan yang tidak dapat memahami kebutuhan pelangan akan memudahkan para pesaing untuk menyerang melalui penawaran produk yang lebih baik yang sesuai dengan keinginan pelanggan (Kaplan dan Norton, 2000).…”
Section: (7)unclassified
“…Total aerobic count and Enterobacteriaceae are common indicators for the three objective measurements in addition to Staphylococcus aureus for employee hand testing and yeast and molds for food packaging material [ 4 , 5 , [13] , [14] , [15] , [16] , [17] ]. Studies in the literature showed that PRPs evaluation were mainly carried out in catering and food production [ 13 , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. However, despite the importance and impact of packaging on all food sectors, no published studies were available in food packaging companies.…”
Section: Introductionmentioning
confidence: 99%
“…Food handlers working in catering establishments are a frequent source of FBD) (Pichiler et al, 2014;Angelo et al, 2017). Inadequate personal hygiene with emphasis on handwashing, cross-contamination, inappropriate hot/cold chain of food are main problems reported in catering establishments (Liz Martins and Rocha, 2014;Tavakkoli et al, 2015;Jev snik et al, 2018) that can contribute to FBD. Thus, the promotion of good hygiene practice among food handlers is the most important food safety preventive action for eliminating pathogen transmission from food handler to the final consumer (Smigic et al, 2016;de Souza et al, 2018) and in particular, adherence to proper hand hygiene is crucial for reducing FBD (Pragle et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…, 2017). Inadequate personal hygiene with emphasis on handwashing, cross-contamination, inappropriate hot/cold chain of food are main problems reported in catering establishments (Liz Martins and Rocha, 2014; Tavakkoli et al. , 2015; Jevšnik et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation